DIGITAL ECONOMY AND EMPLOYMENT - Bustonov, Mansurjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective. The global trend of the twentieth century is the penetration of the Internet into all spheres of life. The transformation of economic activity under the influence of the rapid development of online technologies has led to the formation of the digital economy. Innovative technologies of the digital economy help open up new opportunities - optimization of business processes, costs, open up new directions for attracting capital and promoting business projects. Results.Increasing the efficiency of the digital economy based on modern science and technology, increasing consumer demand for products and services, and providing quality goods through the introduction of new equipment and technologies into the production process has become the leading goal in the world. Today, “the share of the digital economy in the gross domestic product of developed countries is 5.5%, and in developing countries - 4.9%. This figure is 12.4% in the UK, 8% in South Korea, 6.9% in China, 5.6% in India, 2.8% in Russia, 3.9% in Kazakhstan"[1].